Spices for taming the COVID-19 pandemic: Prospects and perspectives: Spices for taming COVID-19 pandemic - A review - Eapen, S J (Journal of Spices and Aromatic Crops, 2021)
Coronavirus Disease 2019 (COVID-19), first reported in December 2019 from Wuhan in China, had reached the stage of a pandemic. To date (28.06.2021), there are more than 181.9 million confirmed cases of the disease in the world. Even though vaccines have been developed, antiviral drugs are yet to be developed for management and treatment of SARS-CoV-2. Since several medicinal plants are used in traditional medicines, though with controversial efficacy claims, they can be considered as sources of new antiviral drug compounds against emerging viruses. In this context, spices are noteworthy as their anti-oxidant, anti-viral, anti-inflammatory and immunostimulatory properties are well studied and documented. The emerging scientific literature includes a number of papers on the anti-SARS-CoV-2 activity of spice extracts and specific compounds proven through different types of laboratory experiments. Here, the information pertaining to anti-viral properties of spice-based phytochemicals or natural compounds (not crude extracts) is summarized in this review. Spice-based compounds discussed here are an option for testing in COVID-19 patients though we don’t have strong data to support their active recommendation. Because of their natural origin, safety, and low cost, they can be a viable option in our fight against viruses and this compilation may be useful for planning and designing more robust experiments in future.